Pewne Problemy Brzegowe dla Ciał Rozdrobionych o Wzmocnieniu Gęstościowym - Mróz, Z.; Kwaszczyńska, K. (Engineering Transactions, 1971)
Consideration is given to a model of a granular medium which is time-independent, elasticplastic, with the yield condition depending on the stress state and the variable material density. Due to density variation, the initial yield surface may expand, contract or undergo more complex changes. Constitutive rate equations are derived and applied to the problem of a thick-walled tube subjected to internal! pressure. Both stable and unstable behaviour is discussed assuming the axi-symmetric deformation mode for large and small plastic deformations.